Progress towards millennium development goal 1 in northern rural Nicaragua: Findings from a health and demographic surveillance site - Pérez Wilton; Blandón Elmer; Persson Lars-Åke; Peña Rodolfo; Källestål Carina (BMC, 2012)
Abstract Background Millennium Development Goal 1 encourages local initiatives for the eradication of extreme poverty. However, monitoring is indispensable to insure that actions performed at higher policy levels attain success. Poverty in rural areas in low- and middle-income countries remains chronic. Nevertheless, a rural area (Cuatro Santos) in northern Nicaragua has made substantial progress toward poverty eradication by 2015. We examined the level of poverty there and described interventions aimed at reducing it. Methods Household data collected from a Health and Demographic Surveillance System was used to analyze poverty and the transition out of it, as well as background information on family members. In the follow-up, information about specific interventions (i.e., installation of piped drinking water, latrines, access to microcredit, home gardening, and technical education) linked them to the demographic data. A propensity score was used to measure the association between the interventions and the resulting transition from poverty. Results Between 2004 and 2009, poverty was reduced as a number of interventions increased. Although microcredit was inequitably distributed across the population, combined with home gardening and technical training, it resulted in significant poverty reduction in this rural area. Conclusions Sustainable interventions reduced poverty in the rural areas studied by about one- third.